Structural basis for the recognition of human cytomegalovirus glycoprotein B by a neutralizing human antibody. - Nadja Spindler (Public Library of Science (PLoS), 2014)
Human cytomegalovirus (HCMV) infections are life-threating to people with a compromised or immature immune system. Upon adhesion, fusion of the virus envelope with the host cell is initiated. In this step, the viral glycoprotein gB is considered to represent the major fusogen. Here, we present for the first time structural data on the binding of an anti-herpes virus antibody and describe the atomic interactions between the antigenic domain Dom-II of HCMV gB and the Fab fragment of the human antibody SM5-1. The crystal structure shows that SM5-1 binds Dom-II almost exclusively via only two CDRs, namely light chain CDR L1 and a 22-residue-long heavy chain CDR H3. Two contiguous segments of Dom-II are targeted by SM5-1, and the combining site includes a hydrophobic pocket on the Dom-II surface that is only partially filled by CDR H3 residues. SM5-1 belongs to a series of sequence-homologous anti-HCMV gB monoclonal antibodies that were isolated from the same donor at a single time point and that represent different maturation states. Analysis of amino acid substitutions in these antibodies in combination with molecular dynamics simulations show that key contributors to the picomolar affinity of SM5-1 do not directly interact with the antigen but significantly reduce the flexibility of CDR H3 in the bound and unbound state of SM5-1 through intramolecular side chain interactions. Thus, these residues most likely alleviate unfavorable binding entropies associated with extra-long CDR H3s, and this might represent a common strategy during antibody maturation. Models of entire HCMV gB in different conformational states hint that SM5-1 neutralizes HCMV either by blocking the pre- to postfusion transition of gB or by precluding the interaction with additional effectors such as the gH/gL complex.